On the Population of Wind-Accreting Neutron Stars in the Galaxy - Pfahl, E; Rappaport, S; Podsiadlowski, P (2002)
We explore the possibility that neutron stars accreting from the winds of main-sequence stellar companions account for a significant fraction of low-luminosity, hard X-ray sources (L_X <~ 10^35 ergs/s; 1-10 keV) in the Galaxy. This work was motivated by recent Chandra observations of the Galactic center by Wang et al. (2002). Our calculations indicate that many of the discrete X-ray sources detected in this survey may be wind-accreting neutron stars, and that many more may be discovered with deeper X-ray observations. We propose that an infrared observing campaign be undertaken to search for the stellar counterparts of these X-ray sources.